Individual responsibility of the Heads of State, Head of Government and the Senior Government Officials for international crime. Voice in discussion - Krawczyk, Przemysław (Studia Iuridica Toruniensia, 2021)
The author of this article, through the analysis of the regulations concerning the immunities of Head of State, Head of Government and Senior Government Officials, tries to answer the question – whether these persons are protected from criminal responsibility for committing an international crime under international criminal law by the immunity they enjoy under both customary and statutory international law. In exploring the issue, examples from the case law of the International Court of Justice and the International Criminal Court are also discussed. The author’s deliberations allow him to conclude that there is nothing like the ‘absolute immunity’ of Head of State, Head of Government and Senior Government Officials in the event of their committing an international crime. Immunity granted to them under international law applies only to “national” crimes, but it does not apply to crimes enshrined in the Rome Statute.